Treatment of Keloids with Surgery and Immediate Postoperative Radiotherapy: Knowledge Gained Over 17 Years - Bhattacharya, Neela; Bhattacharya, Kaushik; Chandran, T.C. (Indian Journal of Plastic Surgery, 2023)
Background The treatment of keloidal scars with radiotherapy has been practiced for more than a century. Radiotherapy post-surgery has been deemed necessary and effective in preventing recurrence but still, no clear guidelines exist as to the best modality of radiotherapy, the ideal dose, and the time it should be given for keloidal scars. The purpose of this study is to confirm the effectiveness of this treatment and address these issues.Methods Since 2004, 120 patients presenting with keloidal scars were seen by the author. Out of them, 50 were managed with surgery followed by HDR brachytherapy/electron beam radiotherapy delivering 2000 rads to the scar within 24 hours of surgery. Patients were followed up for at least 18 months to assess the scar status and the recurrence of keloids. Recurrence was defined as the appearance of a nodule or an obvious return of the keloid within 1 year of treatment.Results Three patients developed a nodule in the scar, which was deemed a recurrence, making an incidence of 6%. There was no major problem after immediate postoperative radiotherapy. Five patients had delayed healing at 2 weeks and a hypertrophic scar was noted in five patients at 4 weeks that settled with conservative measures.Conclusion Treating the vexing problem of keloids with surgery and immediate postoperative radiotherapy is safe and effective. We recommend that this be adopted as the standard treatment in keloid management.
Keywords: keloid; brachytherapy; radiotherapy; hypertrophic scar; keloid excision